Sistem Informasi Penggajian Karyawan Berbasis Web pada Bostown Coffe - Amalia, Fira Rizki; Yasin, Ikbal (Jurnal Media Borneo, 2023)
The development of an employee salary calculation system is a crucial step in enhancing the efficiency and accuracy of human resource management within a company. This research discusses the implementation stages of an employee salary calculation system with a focus on the selection of appropriate tools and technologies. Visual Studio Code is utilized as the development environment, XAMPP serves as the local server, and CodeIgniter is employed as the web development framework. The implemented login menu in the system provides an additional layer of security, ensuring proper access to sensitive data. The use of a local server with XAMPP allows for better testing before the application is deployed in a production environment. The result is an efficient, accurate, and secure system for managing employee salary data, with the potential to enhance productivity and efficiency within the company. By utilizing the right tools and technologies, the implementation of this system provides a solid foundation for effective and controlled human resource management. The test results show that the function of the web-based payroll system application that has been created is functioning well with a total score of 100% in accordance with the functions provided from the system that has been created.